From Gaming to Divination: The Shifting Role of the Lenormand Deck - Xiaoyan Jiang (Studies in Social Science & Humanities, 2024)
This article spotlights the Lenormand deck, from its origins as a playing card for gaming and gambling to its evolving role as a divination tool. By examining the historical context, production techniques, and symbolic imagery, the study highlights the unique cultural and artistic significance of the Lenormand cards. The methodology includes a comparative analysis with the Tarot system, revealing how the Lenormand deck’s straightforward and accessible imagery contrasts with Tarot’s complex esoteric symbolism. This research underscores the Lenormand deck’s reflection of broader societal changes, particularly its role in democratizing art and esoteric practices. The Lenormand’s simplicity and universal symbols made itself accessible to the mass. By situating the Lenormand deck within the broader narrative of cartomancy and visual culture, the essay demonstrates its importance as a historical artifact that bridges gaming, art, and divination, providing insights into the intersection of leisure culture, material history, and social transformation.